Psychological intervention for depression, anxiety, and quality of life in patients undergoing hemodialysis - Putri, Choirunnisa Aprilia Setyo; Putra, Kuswantoro Rusca; Supriati, Lilik (Alma Ata University Press, 2025)
Background: Psychological issues in chronic kidney disease patients undergoing hemodialysis are three times higher compared to other patients. Depression and anxiety in chronic kidney disease patients undergoing hemodialysis are the most significant variables related to the decrease in quality of life.Objectives: This systematic review aims to determine the effectiveness of psychological interventions in reducing levels of depression and anxiety as well as improving the quality of life in patients undergoing hemodialysis.Methods: Articles were identified using online databases such as ProQuest, PubMed, and Science Direct with the keywords Psychological Intervention AND Hemodialysis AND Depression OR Anxiety OR Quality of Life, published between 2020 and 2025. The PICO framework was utilized: patients undergoing hemodialysis with psychological interventions compared to other interventions, with outcomes including levels of depression, anxiety, and quality of life. The selection process was conducted using the PRISMA method, and article evaluation was performed using the Joanna Briggs Institute (JBI) checklist.Results: A total of 16 selected scientific evidences were randomized controlled trials involving 1422 chronic kidney disease patients undergoing hemodialysis, aged 18–80 years. Fifteen types of therapies were identified as potential interventions due to their demonstrated effectiveness among participants, including: cognitive behavioral intervention, cognitive behavioral group therapy, cognitive behavioral intervention + resilience model, multifaceted education, positive thinking training, resilience training, spiritual care, mindfulness meditation + progressive muscle relaxation, recreational therapy, emotional disclosure writing, self-management program, live music, acupressure, aromatherapy massage, and virtual reality exercise.Conclusions: Various types of psychological therapies can serve as effective and efficient intervention options to reduce levels of depression and anxiety, as well as improve the quality of life for chronic kidney disease patients undergoing hemodialysis.